Evaluation of hepatitis B virus transmission and antiviral therapy among hepatitis B surface antigen‐positive pregnant women. Issue 12 (14th September 2015) - Tekin Koruk, Suda; Batirel, Ayse; Kose, Sukran; Cetin Akhan, Sila; Aygen, Bilgehan; Tulek, Necla; Hatipoglu, Çigdem; Bulut, Cemal; Yıldız, Orhan; Sacligil, Cahide; Sirmatel, Fatma; Altunok, Elif
Abstract: Aim: The aim of the present study was to assess the potential risk of hepatitis B virus (HBV) vertical transmission among Turkish parturient women and to evaluate the efficacy and safety of antiviral agents. Material and Methods: Data were collected retrospectively from 114 HBV‐infected pregnant women and their infants in eight health institutions in Turkey. Results: The baseline characteristics of the women were: mean age, 28.3 ± 5.2 years; alanine aminotransferase, 57.4 ± 139.0 U/L; aspartate aminotransferase, 56.6 ± 150.0 U/L; and HBV DNA, 8.3 × 10 7  ± 2.6 × 10 8 copies/mL. Family history of HBV infection was detected in 53.5% ( n  = 61). In total, 60 (52.6%) pregnant women received tenofovir (60.0%), lamivudine (33.3%) or telbivudine (6.7%) therapy at the median gestational age of 22.2 ± 8.5 (1–36) weeks. All infants were vaccinated and hepatitis B immune globulin was administered, with 81 of them (71.1%) available for follow‐up. After completion of HBV vaccination course, 71 (87.7%) infants had protective anti‐HBs levels, three (3.7%) were hepatitis B surface antigen‐positive, and seven (8.6%) were hepatitis B surface antigen‐negative with nonprotective anti‐HBs levels. Five of the infants had low gestational birthweight but no other birth defects were observed. Conclusion: According to our results, viral load may not be the only effecting factor for transmission of HBV to children of infected mothers. Pregnant women with high viral load should be followed‐up closely during pregnancy. They should begin to take tenofovir or telbivudine, which are category B drugs for pregnancy, at the beginning of the third trimester at the latest. We need new treatment strategies; and close follow‐up of mothers and children is another important issue.